Adjuvant yoga therapy for symptom management of functional dyspepsia: A case series - Garima Setia; Meena Ramanathan; Ananda Balayogi Bhavanani; B Sajeeth Manikanda Prabu; Vinoth B; Ananthkrishnan N (Journal of Ayurveda and Integrative Medicine, 2023)
Functional Dyspepsia (FD), commonly called chronic indigestion, comes under the umbrella of 'Disorders of Gut–Brain Axis'. It manifests as a cluster of upper gastrointestinal symptoms including epigastric pain or burning, postprandial fullness and early satiety. Since the pathophysiology is complex, it is often difficult to effectively manage and significantly impacts the patient's quality of life. This case series aims to elucidate the role of Yoga as an adjuvant therapy to modern medicine in providing relief of dyspeptic symptoms in such patients. Yoga is an ancient Indian mind-body practise that has the potential to be used for various brain-gut disorders. Apart from treating the gut disorders from top down (mind-gut) pathway, it may have more direct physiological effects as well. Researches on IBS and one research on abdominal pain related FGID have shown Yoga therapy to be effective in ameliorating the symptoms.In this study, we present three such cases (1 male and 2 female) having a clinical diagnosis of FD in detail. These patients were initially non-responsive to medications but later showed remarkable improvement in symptoms within one month of added Yoga therapy intervention. This study was conducted as a part of a larger study conducted at a tertiary hospital in Pondicherry in collaboration between its Yoga department and Medical Gastroenterology Department. Yoga therapy protocol was given along with their regular medical management for a month. Gastrointestinal Symptom Rating Scale (GSRS) and Dyspepsia Symptom Score questionnaires were used to assess symptoms before and after the intervention period. All three patients showed marked reductions in symptom scores both in the GSRS and Dyspepsia Questionnaire. The present case series suggests effect of adjuvant Yoga therapy in reducing symptoms of functional dyspepsia. Future studies may clarify the psycho-physiological basis of the same.